Konseling Perilaku Kognitif Sinkretik: Mengembangkan Makna Hidup Siswa melalui Paduan Nilai-Nilai Budaya Islam dan Osing - Husni Hanafi; Nur Hidayah; Andi Mappiare; Nordin Bin Mamat (State Islamic University (UIN) Salatiga, 2025)
The Osing culture embodies syncretic values that influence individuals respond to life’s challenges and shape their values and belief as part of their meaning of life (MoL). This study aimed to examine the effectiveness of integrating Osing cultural syncretism into Cognitive Behavioral Counseling (CBC) to support students in developing MoL based on creative, experiential, and attitudinal dimensions. A quasi-experimental pretest-posttest design was used, involving 30 students from the Osing ethnic group by purposive sampling. Data were collected using the Meaning of Life Questionnaire (MLQ), adapted to reflect Osing cultural constructs, supported with alpha reliability at .769. The results were analyzed using a paired-sample t-test. Findings revealed a significant positive difference in students’ MoL scores after the intervention, supporting the effectiveness of the syncretic CBC model as the significant value below .001. The blended Osing cultural and Islamic values had become syncretism practices in the community spiritual dimension. This contributes in counseling for students’ cognitive reframing and value-based decision-making. Syncretism serves as a foundation for belief systems and automatic thought patterns. This study suggests culturally grounded counseling to enhance psychological outcomes based on exploration of Osing spiritual-cultural practices, like Barong Ider Bumi, Tumpeng Sewu, and other local wisdoms.